Periody individual'nogo goda, trebujuscie vnimanija vracej i trenerov - Saposnikova, V. I. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The cardiovascular pathology draws the attention of cardiologists of all countries. These diseases began to be shown at young people and even in athletes. The purpose of the research was the studying of the parameters describing the functional condition of a heart in interrelation with month's of the annual endogenous cycle. The results of the research allow to pay the special attention of physicians and coaches to the periods of the individual year of athletes when the risk of diseases of the cardiovascular system grows. It is necessary to individualize the medical supervision over parameters of the arterial pressure and the functional condition of the heart of an athlete in such periods and also to take them into the account at planning of a high training loadings.